2008
DOI: 10.1111/j.1464-410x.2008.07499.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablative response of prostate cancer cells is influenced by androgen receptor expression

Abstract: OBJECTIVE To investigate in prostate cancer cells the consequences of androgen‐insensitivity (AI) development on the cellular and molecular responses to freezing, as a challenge in prostate cancer treatment occurs when the androgen‐sensitive (AS) phenotype switches to an AI phenotype, the latter of which is often refractory to many therapies. MATERIALS AND METHODS PC‐3 (AI) and LNCaP (AS) were each genetically altered to express the opposite phenotype and subjected to an in vitro freezing model. Viability, cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 23 publications
(40 reference statements)
1
28
0
Order By: Relevance
“…37 Despite the approximately 50% cell death expressed following exposure to À15 C, these reports have shown that complete destruction of prostate cancer cells is not achieved until temperatures reach À40 C or below in vitro. [26][27][28]35,37 In regard to PaCa cells, in this study, we observed a moderate impact on the viability at À15 C or warmer, whereas temperatures below À20 C resulted in a more severe decrease in cell viability. Gage et al suggest that while temperatures within the range of À20…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…37 Despite the approximately 50% cell death expressed following exposure to À15 C, these reports have shown that complete destruction of prostate cancer cells is not achieved until temperatures reach À40 C or below in vitro. [26][27][28]35,37 In regard to PaCa cells, in this study, we observed a moderate impact on the viability at À15 C or warmer, whereas temperatures below À20 C resulted in a more severe decrease in cell viability. Gage et al suggest that while temperatures within the range of À20…”
Section: Discussionmentioning
confidence: 63%
“…Fluorescence microscopy indicated that the different cells subjected to the same exposures experienced varying levels of cell death at different points within the initial 24 hours postexposure ( Figure 3). These results indicate that, as with other cancers, [25][26]35 PaCa molecular variants exhibit differential responses to mild thermal treatment. However, these data suggest that when a critical temperature threshold is surpassed (<À25 C or >50 C), complete cell death results regardless of the molecular disposition.…”
Section: Comparison Of Thermal Sensitivity Of Paca Cellsmentioning
confidence: 71%
See 1 more Smart Citation
“…Slow permeation of CPA in cornea and cartilage has been reported, possibly due to the presence of highly charged GAG (Klossner et al, 2008) and collagenous network (Maroudas, 1976;Walcerz et al, 1995). The IVD being a GAG-and collagen-rich tissue (Roberts and Caterson, 2004), might behave similarly with slow CPA permeation.…”
Section: Scw Chan Et Al Cryopreservation Of Whole Intervertebral Discsmentioning
confidence: 93%
“…Baust et al examined survival rates of in vitro prostate and colorectal cancer cell lines after a single cycle of cryoablation and found an increased cell survival rate when the cells were exposed to caspase inhibitors (12). Another study by Klossner et al demonstrated that androgen insensitive prostate cancer cell lines showed significantly increased survival rates versus androgen sensitive cell lines after treatment (13). There are, however, also encouraging indications that adjuvant therapies may increase tumor sensitivity to cryotherapy.…”
Section: Figure 1 -A) Closest To the Cryoablation Probe Rapid Coolinmentioning
confidence: 99%